In vitro Synergistic Activity of Antimicrobial Combinations Against blaKPC and blaNDM-Producing Enterobacterales With blaIMP or mcr Genes - Zhou, Chaoe; Wang, Qi; Jin, Longyang; Wang, Ruobing; Yin, Yuyao; Sun, Shijun; Zhang, Jiangang; Wang, Hui (Frontiers in Microbiology, 2020)
Carbapenemase-producing Enterobacterales have become a severe public health concern because of their rapidly transmissible resistance elements and limited treatment options. The most effective antimicrobial combinations against carbapenemase-producing Enterobacterales are currently unclear. Here, we aimed to assess the therapeutic effects of seven antimicrobial combinations (colistin-meropenem, colistin-tigecycline, colistin-rifampicin, colistin-erythromycin, meropenem-tigecycline, meropenem-rifampicin, and meropenem-tigecycline-colistin) against twenty-four carbapenem-producing Enterobacterales (producing blaKPC, blaNDM, coexisting blaNDM and blaIMP, and coexisting mcr-1/8/9 and blaNDM genes) and one carbapenem-susceptible Enterobacterales using the checkerboard assay, time-kill curves, and scanning electron microscopy. None of the combinations were antagonistic. The combination of colistin-rifampicin showed the highest synergistic effect of 76% (19/25), followed by colistin-erythromycin at 60% (15/25), meropenem-rifampicin at 24% (6/25), colistin-meropenem at 20% (5/25), colistin-tigecycline at 20% (5/25), and meropenem-tigecycline at 4% (1/25). The triple antimicrobial combinations of meropenem-tigecycline-colistin had a synergistic effect of 100%. Most double antimicrobial combinations were ineffective on isolates with coexisting blaNDM and blaIMP genes. Meropenem with tigecycline showed no synergistic effect on isolates that produced different carbapenemase genes and were highly resistant to meropenem (92% meropenem MIC ≥ 16 mg/mL). Colistin-tigecycline showed no synergistic effect on Escherichia coli producing blaNDM–1 and Serratia marcescens. Time-kill curves showed that antimicrobial combinations achieved an eradication effect (≥ 3 log10 decreases in colony counts) within 24 h without regrowth, based on 1 × MIC of each drug. The synergistic mechanism of colistin-rifampicin may involve the colistin-mediated disruption of bacterial membranes, leading to severe alterations in their permeability, then causes more rifampicin to enter the cell and induces cell death. In conclusion, the antimicrobial combinations evaluated in this study may facilitate the successful treatment of patients infected with carbapenemase-producing pathogens.